Influência de três tratamentos de superfície para cerâmicas a base de zircônia na resistência adesiva e no comportamento à fadiga do material - Amaral, Marina [UNESP] (2014)
The aim of this study is to evaluate the effect of different silica deposition methods on the surface of a zirconia ceramic on the adhesion to a resin cement and on the fatigue limit of the materials. The tested hypothesis is that surface treatments enhance the adhesion of resin cement to zirconia, and that the application of a silica layer reduces the flexural strength of zirconia discs, before and after mechanical cycling, and that air abrasion enhance the strength in both situations, following this patter also to fatigue limits. For the adhesive test, 45 bars received the following surface treatments (n = 15): control: without surface treatment after sintering; air-abrasion: 30 μm SiO2 particles (Rocated Soft, 3M ESPE); glaze: application of a thin layer of glaze (Glaze Vita Akzent - Vita Zanhfabrik), HF etching during 1 min plus silane. Samples were resin cemented to lithium dissilicate slices, and after 2,500 cycles of thermocycling, the tensile test was performed. Disc-shaped specimens were used for the evaluation of mechanical properties. The same surface treatments were performed on the tensile side of the samples. Specimens were submitted to biaxial flexural strength before and after mechanical cycling (2 x 106 cycles, 100 N, water immersion 37 ºC, 4 Hz). Stair case method was used to determine the fatigue limit of samples at 102, 103, 104 and 105 cycles. Adhesive strength was higher for air abraded group, compared to glaze group; control group did not survived thermocycling. Mechanical cycling had no effect on flexural strength. Air abrasion presented the highest values of flexural strength. Weibull analysis showed the highest m value for air abraded group without mechanical cycling, and the highest value was presented by glazed and mechanical cycled group. In stair case analysis, all groups presented a decrease in fatigue limit according to increase in number of cycles; air ...